JESSICA and urban development funds — new duties for old regional development companies? - Held, Tobias; Jakubowski, Peter (Raumforschung und Raumordnung | Spatial Research and Planning, 2009)
The JESSICA-initiative of the European Commission and the European Investment Bank allows implementing innovative instruments to enhance investments in sustainable urban development. This article analyzes possible duties of the German regional development companies in the new field of urban development funds. As they are experienced players in the compliance of public objectives of urban development, the regional development companies have profound knowledge of the JESSICA-approach’s core areas. Given their experience in the field, the regional development companies could assume the selection and the control of urban development projects within a new structure of public private partnership in an urban development fund.